Shorter height is associated with diabetes in women but not in men: nationally representative evidence from Namibia - Koncz, Viola; Geldsetzer, Pascal; Manne-Goehler, Jennifer; Wendt, Amanda; Teufel, Felix; Subramanian, S. V.; Bärnighausen, Till; De Neve, Jan-Walter (Obesity, 2019)
Objective This study aimed to test the hypothesis that attained adult height, as an indicator of childhood nutrition, is associated with diabetes in adulthood in Namibia, a country where stunting is highly prevalent. Methods Data from 1,898 women and 1,343 men aged 35 to 64 years included in the Namibia Demographic and Health Survey in 2013 were analyzed. Multiple logistic regression models were used to calculate odds ratios (ORs) and 95% CIs of having diabetes in relation to height. The following three models were considered: Model 1 included only height, Model 2 included height as well as demographic and socioeconomic variables, and Model 3 included body mass index in addition to the covariates from Model 2. Results Overall crude diabetes prevalence was 6.1% (95% CI: 5.0-7.2). Being taller was inversely related with diabetes in women but not in men. In Model 3, a 1-cm increase in women’s height was associated with 4% lower odds of having diabetes (OR, 0.96; 95% CI: 0.94-0.99; P = 0.023). Conclusions Height is associated with a large reduction in diabetes in women but not in men in Namibia. Interventions that allow women to reach their full growth potential may help prevent the growing diabetes burden in the region.
Gesehen am 28.03.2019